NALAR FIKIH MAZHAB SYAFI’I DALAM KASUS PERNIKAHAN WANITA HAMIL DAN STATUS ANAK YANG DILAHIRKAN - Muhammad Abdulloh Rohmad Azis; Sadari Sadari (LPPM UNHASY, 2023)
This article is the result of library research. This study aims to: track the shafi'iyah school of thought in determining the legal status of pregnant women marriage. This article discusses the reasoning or way of thinking of the Shafi'iyah school in determining the legal status of a pregnant woman's marriage and the status of the child she gives birth to. The claim of this research is that the approach taken by the syafi'iyah school in determining the legal status of pregnant women's marriages uses a textual approach. The source of the law used is the Hadith of the Prophet Muhammad which stipulates that a wife who is still in her husband's marriage contract, every child born to her, even though it is the result of adultery, is considered by law to be her husband's child. The results of this study conclude that a child born before a legal marriage, is considered an adulterous child, cannot be attributed to a father, and each of them cannot be an heir and neither can inherit. If the marriage is carried out to cover the disgrace, if it is carried out before six months of gestation, the status of the baby is considered a legal child according to Islamic law. Keywords: jurisprudence reasoning, shafi'i school, marriage of pregnant women Daftar Pustaka Abdul Azis Dahlan, Ensiklopedi Hukum Islam, cet. 1 (Jakarta: Ichtiar Baru Van Hoeve, 1996) Abdul Haq, Formulasi Nalar Fiqih Telaah Kaidah Fiqih Konseptual, Buku kedua, (Surabaya Kaki lima, 2006) Abdur Rahman Ghazali, Fiqih Munakahat, (Jakarta: Prenada Media, 2003) Abdurrahman Al-Jaziri, al-Fiqh ala al-Madzahib al-arbaah, (Beirut, Libanon Dar al-kutub al-ilmiah, jilid IV, cet.IV) ––––––––, Kitab al-Fiqh (Mesir, Maktabah al-Tijāriyyah al-Kubrā, 1969 Abdurrahman Al-Jaziry, al -Fiqh 'ala Madzahtbi al-Arba'ah Juz IV, (Beirut Darul Haya'al-Turbal-Araby, 1969) Abduttawab Hakal, Rahasia Perkawinan Rasulullah Poligami dalam Islam vs Monogami Barat (Cet. I; Jakarta: Pedoman Ilmu Jaya, 1993) Abû al-Fidâ al-Hafizh ibn Katsîr al-Dimasqî, Al-Bidâyah wa al-Nihâyah, (Beirut: Dâr al-Kutub al-‘Ilmiyyah, t.t.) Abu Daud, Sulaiman Al-Jistani, Sunan Abi Daud, Mushhaf al-Baby ai-Halaby, Mesir Abû Hâmid Muhammad ibn Muhammad ibn Muhammad al-Ghazâlî, Al-Mustashfâ, (Beirut: Dâr al-Fikr, 1998) Abû Ishâq al-Fayruzabadî al-Syayrâzî, Al-Lumâ’ fi Ushûl al-Fiqh Abû Zahrah, Târîkh Madzâhib al-Fiqhiyyah, (Kairo: Mathba’ah al-Madanî, t.t.) Ahmad Hasan, Analogical Reasoning in Islamic Jurisprudence, (Delhi: Adam Publisher, 1994) Ahmad Hasan, Pintu Ijtihad Sebelum Tertutup, terj oleh Agah Garnadi (Bandung: Pustaka, 1994) Ahmad Muhammad al-Syâkir, di dalam komentar al-Risâlah, (Beirut: Dâr al-Fikr, 2005) Ahmad Rofiq, Fiqh Mawaris Edisi Revisi (Jakarta: Raja Grafindo Persada, 2001) Al Amin, Habibi.